Effects of Parathyroid Hormone Administration on Bone Strength in Hypoparathyroidism - Rubin, Mishaela R. (J Bone Miner Res, 2016)
The microstructural skeletal phenotype of Hypoparathyroidism (HypoPT), a disorder of inadequate parathyroid hormone secretion, is altered trabecular microarchitecture with increased trabecular bone volume and thickness. Using 2-D histomorphometric analysis, we previously found that 2 years of PTH(1–84) in HypoPT is associated with reduced trabecular thickness (Tb.Th) and an increase in trabecular number (Tb.N). We have now utilized direct 3-D microstructural analysis to determine the extent to which these changes may be related to bone strength. Iliac crest bone biopsies from HypoPT subjects (n=58) were analyzed by microcomputed tomography (µCT) and by microfinite element (µFE) analysis. Biopsies were performed at baseline and at 1 or at 2 years of recombinant human PTH(1–84) [rhPTH(1–84)]. In a subset of subjects (n=13) at 3 months, we demonstrated: a reduction in trabecular separation (Tb.Sp, 0.64 ± 0.1 to 0.56 ± 0.1 mm; p=0.005) and in the variance of trabecular separation (Tb.SD, 0.19 ± 0.1 to 0.17 ± 0.1 mm; p=0.01), along with an increase in bone volume/total volume (BV/TV, 26.76±10.1 to 32.83±13.5%; p=0.02), bone surface/total volume (BS/TV, 3.85 ± 0.7 to 4.49 ±1.0 mm(2)/mm(3); p=0.005), Tb.N (1.84 ± 0.5 vs 2.36 ± 1.3 mm(−1); p=0.02) and Young’s modulus (649.38±460.7 to 1044.81±1090.5 N/mm(2); p=0.049). After 1 year of rhPTH(1–84), Force increased (144.08±102.4 to 241.13±189.1 N; p=0.04) and Young’s modulus tended to increase (662.15±478.2 to 1050.80 ±824.1 N/m(2); p=0.06). The 1 year change in cancellous mineralizing surface (MS/BS) predicted 1 year changes in µCT variables. The biopsies obtained after 2 years of rhPTH(1–84) showed no change from baseline. These data suggest that administration of rhPTH(1–84) in HypoPT is associated with transient changes in key parameters associated with bone strength. The results indicate that rhPTH(1–84) improves skeletal quality in HypoPT early in treatment.